Unique intrahepatic transcriptomics profiles discriminate the clinical phases of a chronic HBV infection. - Jun Hou; Willem P Brouwer; Kim Kreefft; Lucio Gama; Sarah L Price; Harry L A Janssen; Pim J French; Thomas Vanwolleghem; Andre Boonstra (PLoS ONE)
Chronic hepatitis B is a highly heterogeneous liver disease characterized by phases with fluctuations in viral replication and progressive liver damage in some, but not all infected individuals. Despite four decades of research, insight into host determinants underlying these distinct clinical phases-immunotolerant, immune active, inactive carrier, and HBeAg-negative hepatitis-remains elusive. We performed an in-depth transcriptome analysis of archived FFPE liver biopsies of each clinical phase to address host determinants associated with the natural history. Therefore, we determined, for the first time, intrahepatic global expression profiles of well-characterized chronic HBV patients at different clinical phases. Our data, obtained by microarray, demonstrate that B cells and NK/cytotoxic-related genes in the liver, including CD19, TNFRSF13C, GZMH, and KIR2DS3, were differentially expressed across the clinical HBV phases, which was confirmed by modular analysis and also Nanostring arrays in an independent cohort. Compared to the immunotolerant phase, 92 genes were differentially expressed in the liver during the immune active phase, 46 in the inactive carrier phase, and 71 in the HBeAg-negative phase. Furthermore, our study also revealed distinctive transcription of genes associated with cell cycle activity, NF-κB signaling, cytotoxic function and mitochondrial respiration between clinical phases. Our data define for the first time using microarray unique transcriptomes in the HBV-infected liver during consecutive clinical phases. We demonstrate that fluctuations of viral loads and liver damage coincide with fluctuations in the liver transcriptome and point to functional- immune and non-immune- components contributing to the clinical phenotype in patients.